Shrines and identities in Britain’s Nepali diaspora - Gellner, D; Hausner, S; Laksamba, C; Adhikari, K (University of Toronto Press, 2016)
This article examines the tension between publicly affirmed religious identification and private religious practice among Britain’s Nepali diaspora population. It compares census and survey figures for religious affiliation with religious shrines in people’s homes. In some cases there is complete congruence between religious affiliation and home worship (most strikingly in the cases of Sherpas, whose affiliation and shrines are unequivocally Buddhist). Among many other groups, however, there is plenty of evidence of multiple belonging. The most common case is singular identification for census purposes and multiple practice, but there are also many instances of multiple identification when offered the opportunity. For example, when asked for their religion, Gurungs frequently affirm a Buddhist identity, but when given the option to be both Hindu and Buddhist, they frequently embrace it as it more closely describing their actual practice. Many Kirats keep no shrine at home because they believe that their tribal tradition is properly aniconic. Our material clearly shows that the distribution of ecumenical attitudes is not random, but reflects particular ethnic, regional, and caste histories within Nepal. The ethnic/caste makeup of Britain’s Nepali diaspora is not identical to that of Nepal, mainly because of the history of Gurkha recruitment, and this demographic shift is reflected in the higher proportion of Buddhists in Britain. Nonetheless, we suspect that the findings of this study would be replicated in an urban context in Nepal.